Extremely Rare Case of Successful Treatment of Foot Ulcer Associated with Evans’ Syndrome and Buerger’s Disease - Ha-Jong Nam; Se-Young Kim; Je-Yeon Byeon; Hwan-Jun Choi (Medicina, 2024)
Evans Syndrome (ES) is a rare autoimmune disorder characterized by the simultaneous occurrence of immune thrombocytopenia (ITP) and autoimmune hemolytic anemia (AIHA). Thrombotic complications in ES patients are uncommon, particularly involving Buerger’s Disease (BD). We report a case of a 49-year-old male with ES and a history of diabetes and heavy smoking, presenting with a necrotic wound on his right great toe. Diagnostic evaluations revealed severe stenosis and thrombosis in the lower limb arteries, diagnosed as BD. The patient underwent successful popliteal–tibioperoneal artery bypass surgery and the subsequent disarticulation and revision of the distal phalanx, followed by the application of an acellular dermal matrix (ADM) to promote healing. Post-surgery, the patient showed significant improvement in blood flow and complete epithelialization without complications. This case highlights the importance of a multidisciplinary approach to managing complex wounds in ES patients, suggesting potential treatment pathways for future cases involving BD.